Understanding the Extent of Doctor’s Liability in Medical Disputes - R, Bella Agatha Fernando; Budiarsih, Budiarsih (Rechtsnormen: Journal of Law, 2023)
Background. In order to protect themselves from the possibility of being arrested and subjected to criminal penalties, doctors developed defensive medicine, which is currently being widely applied by many doctors. This is motivated by a situation where the patient is dissatisfied with the results of the medical action that has been carried out and complains about this to the police and some patients often do not want to use the mediation first, then cases like this will end up in court. Purpose. The purpose of this research is to explain how responsibility is imposed on doctors for medical disputes and violations that occur to patients. Method. This type of research is normative, the writer also uses statute approach and conceptual approach to analyze the issue. Results. Based on the background problems, the results obtained from this research are that a doctor who has carried out their duties in accordance with professional standards, service standards, and standard operating procedures is entitled to legal protection. Conclusion. An action can be said to be malpractice if an element of negligence is found in the medical action, whereas in medical risk there is no element of negligence. That if a mistake cannot be found, the doctor cannot be held responsible.